Direct digital control in heating, ventilating and air-conditioning in a class 100 clean room - Li, Xingjun. (2008)
This dissertation describes a methodology for the HVAC system and the DDC control system. Electronic analog controllers, sensors, and actuators have been successfully applied to these critical control requirements.